Images at the crossroads: media and meaning in Greek art - Barringer, Judith M.; Lissarrague, François (Edinburgh Leventis studies, 2022)
New studies on the interaction of various media in ancient Greek artThis collection includes twenty-one new essays by leading scholars in the field of Greek art and archaeology. Exploring a range of media including vase painting, sculpture, gems and coins, they each address questions that cross the boundaries of specialised fields.They outline the range of visual experiences at stake in the various media used in antiquity and shed light on the specificities of each medium. They show how meaning is produced, according to the nature of the medium: its use, context and enunciative structure. Also explored are the different methodologies used to produce meaning: how do images ‘make’, or create, sense to their ancient viewers and how can we now access those meanings?This richly illustrated volume offers new interpretations and arguments concerning fundamental questions in the field which expands our knowledge and understanding of Greek art, patrons and viewers